Gestão ambiental como elemento da estratégia empresarial: um estudo longitudinal em uma empresa têxtil - Santos, Ricardo Ribeiro (2007)
The objective of this work is to evaluate, through the Environmental-SCP model, the strategies adopted by a Brazilian textile company. In this context, it shows a longitudinal analysis of environmental strategies adopted by the company for eleven years, from 1996 to 2006. The research was based on an environmental strategy evaluation model, called Environmental-SCP model, proposed by Abreu (2001). The model links environmental performance to the conducts of the companies exposed to the pressure of the industry in which they operate. Thus, it was identified the environmental pressures, conducts and performance of the company in the last eleven years. Finally, this work presents the company´s strategic positioning, in the last eleven years, face to environmental questions. This strategic positioning is determined from the matrix that clusters companies depending on their environmental behavior and industry structure pressure according to Environmental-SCP. The analyzed company is a large scale textile firm in Ceará state that maintains an environmental management system certified according to ISO 14001 since 2001. The data were collected through document analysis and structured interviews with employees. The data were organized in electronic spreadsheets for qualitative and quantitative analysis. From this analysis, three stages of environmental strategy were identified in this period. The first stage management was unaware of environment-related pressures and merely adopted environmental conducts with the aim of acquiring obligatory environmental license. In the second stage, the perception of external though as yet unthreatening pressures led to the implementation of an environmental management system. In the third stage, as response to increased environmental pressures threatening the company´s competitiveness and in consideration to demands expressed by stakeholders, management adopted environmental conducts while making processes more efficient and created a competitive advantage. This study showed the company´s change from relative indifference to an environmentally responsible attitude harmonizing pollution prevention and increased process efficiency.